Perawatan Diri Sebagai Habitus Mahasiswa Laki-Laki Di Next Premium Barbershop Medan - Ratih Baiduri; Wardah Khoiriah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This study aims to determine the background or reasons why male students care about a treatment, what types of self-care they do, and how the impact they feel after doing self-care. This study discusses a habitus or men's habits in caring for themselves so that the theoretical review used in this study is the Habitus theory of Pierre Bourdiue. This type of research is qualitative research that is collected through direct observation, in-depth interviews, literature study, and documentation. The location of this research was conducted at Next Premium Barbershop Medan by taking 5 informants, namely students who were maintenance customers at the barbershop. The results of this study are the background of male students doing self-care to form a self-image such as wanting to look cooler, fashionable, attractive, neat and clean, then because they enjoy the fun with the comfort provided by barbershop, another reason is due to environmental factors such as friends and campus environment, the types of self-care they do are hair care and facial care, there are several impacts they feel after doing self-care, the positive impact is that male students become more confident and often get praise from the surrounding environment while the negative impact self-care is a matter of care costs and they consciously admit that this habit or habit of caring for themselves causes a consumerist effect that makes them dependent on self-care.